A Tribute to H. George Fredrickson. Issue 1 (18th March 2021) - Dubnick, Melvin J; Guy, Mary E; Kettl, Donald F; Kim, Pan Suk; O'Leary, Rosemary
Abstract: During his 50-year career, H. George Frederickson contributed on multiple fronts: to better government, to a more thoughtful and rigorous public administration field, to better scholarship, to a network of scholars, and to collaborative interaction among practitioners and scholars. He was the founding Editor of the Journal of Public Administration Research and Theory as well as the Journal of Public Administration Education . He was one of the founders of the Public Management Research Association (PMRA) and was instrumental in establishing the world headquarters of PMRA at the University of Kansas School of Public Affairs, where he was the Edwin O. Stene Distinguished Professor. He was President of Eastern Washington University. A gifted writer and thinker who excelled in both breadth and depth, George published important articles and books, and won many awards for his scholarship. Most importantly, he was a catalyst for establishing social equity as the "third pillar" of public administration. In this article, five public administration scholars pay tribute to H. George Frederickson's most influential scholarly works, with an emphasis on social equity and accountability. George's impact outside of the United States, especially in South Korea, also is highlighted.